2014
DOI: 10.3109/02699052.2014.954271
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of age and gender factors in prolonged post-concussion symptoms after mild head injury

Abstract: Older age and female gender are vulnerability factors in the development of prolonged PCS. The main clinical implications are for how early intervention and reassurance are best provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…Sex, psychiatric history (present/absent), and compensationseeking status (at time 1) were entered as covariates because of their well-documented association with MTBI outcome. 30,31 The overall model was significant (χ 2 = 10.03, P = .018). Female sex (OR = 4.40; 95% CI, 1.10-14.99) and a positive psychiatric history (OR = 5.90; 95% CI, 1.29-27.03) were independently associated with high symptoms 1 year after MTBI.…”
Section: Resultsmentioning
confidence: 92%
“…Sex, psychiatric history (present/absent), and compensationseeking status (at time 1) were entered as covariates because of their well-documented association with MTBI outcome. 30,31 The overall model was significant (χ 2 = 10.03, P = .018). Female sex (OR = 4.40; 95% CI, 1.10-14.99) and a positive psychiatric history (OR = 5.90; 95% CI, 1.29-27.03) were independently associated with high symptoms 1 year after MTBI.…”
Section: Resultsmentioning
confidence: 92%
“…It is an 8-point ordinal scale divided into upper and lower levels of good recovery (7, 8), moderate disability (5, 6), severe disability (3, 4), vegetative state (2), and death (1). …”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review, Silverberg et al (7) found that potential contributors include preinjury factors (demographic variables including female gender (8), advanced age (8), being single, lower education, poor preinjury health, preinjury functioning, and low level of resilience), injury-related factors (mechanism of injury, severity of MTBI in terms of longer posttraumatic amnesia (PTA) duration, lower Glasgow Coma Scale (GCS) score, and loss of consciousness (LOC), and alcohol intoxication), and postinjury coexistence of pain, posttraumatic stress, anxiety and depression, and negative expectations (7). …”
Section: Introductionmentioning
confidence: 99%
“…For example, conservative estimates of anterior cruciate ligament (ACL) injuries in team ball sports such as soccer and basketball report females having 2–3 times greater numbers of ACL injuries than males 9–11. Similarly, several systematic reviews have reported sex differences in reported concussion incidence,12–16 risk factors13 17 18 and outcomes 12 19 20. In light of these findings, in other sports it is reasonable to think that there may be differences in the types of injuries sustained by male and female participants of AF.…”
Section: Introductionmentioning
confidence: 92%